Qualitative Analysis of Single-Site Headache Surgery: Is It Different From Multiple-Site Surgery?. Issue 1 (July 2021) - Israel, Jacqueline S.; Gutierrez-Meza, Diana; Albano, Nicholas J.; Smith, Jeremy P.; Abd-Elsayed, Alaa; Schwarze, Margaret L.; Macdonald, Cameron L.; Afifi, Ahmed M.
Abstract : Background: Migraine surgery has been shown to be efficacious, but nuanced effects of surgery on pain and individuals' lives remain incompletely understood. Surgery may be performed at a single or multiple "primary" sites. The aims of this study were to investigate patient perceptions following single-site surgery and compare themes in patients undergoing single-site surgery with those from a previously published conceptual framework generated with patients undergoing multisite surgery. Methods: Patients who underwent single-site headache surgery participated in open-ended interviews at least 1 year after surgery. Participants (n = 14) had undergone either occipital, temporal, or nasoseptal site surgery. A multidisciplinary team analyzed transcripts. Recurring themes were identified and compared and contrasted to those observed in patients who underwent multiple-site surgery (n = 15) in a previous study ( Plast Reconstr Surg 2019;144(4):956–964). Results: Similar recurring themes emerged from the single-site cohort, and the conceptual framework was applicable to all participants. Two new themes emerged from the single-site analysis. First, 5 of 14 participants described being "migraine-free" postoperatively, a finding not observed in the multisite group. Second, several individuals described financial benefits after surgery, via decreased prescription medication requirements, raises at work, and improved productivity. Conclusions: Single-site headache surgery appears to positively impact patients' lives in ways that support and expand upon previously published outcomes. Patients undergoing surgery at a single site may be more likely to experience a "pain-free" state, which may relate to the underlying pathophysiology of chronic headache. The effect of surgery on finances appears to be an outcome of interest to patients, which should be explored further.